Biological biogas upgrading in a membrane biofilm reactor with and without organic carbon source. (September 2021) - Miehle, Maximilian; Hackbarth, Max; Gescher, Johannes; Horn, Harald; Hille-Reichel, Andrea
Graphical abstract: Highlights: Ex-situ and combined ex- and in-situ biogas upgrading proved feasible in a MBfR. In-situ upgrading leads to thicker biofilms by growth of acetoclastic archaea. Controllability of gas quality is highest for ex-situ hydrogenotrophic methanation. Abstract: Biogas upgrading is a necessary step to minimize the CO2 of raw biogas and to make it suitable for gas liquefaction or introduction into the national gas grid. Biomethanation is a promising approach since it converts the CO2 to more methane on site, while taking advantage of the organisms responsible for biogas production in the first place. This study investigates the suitability of a pseudo-dead-end membrane biofilm reactor (MBfR) for ex-situ biogas upgrading using biogas as sole carbon source as well as for additional acetoclastic methanation when an organic carbon source is provided. Results prove that the concept of MBfR is especially advantageous for ex-situ hydrogenotrophic methanation of biogas CO2, yielding high product gas qualities of up to 99% methane. It is discussed that cross-flow membrane operation could reduce mass flux of inert methane through membranes, attached biofilms, and reactor liquid, and, thus, improve methanation space time yields.